Variation in thoracic wall thickness on multi-detector CT in adult patients and its implications in needle thoracostomy for tension pneumothorax - Chang, Ju-Mei (Division of Radiology, 2023)
Background: Traditional treatment guideline for chest trauma to prevent tension pneumothorax is needle thoracostomy with a large-calibre catheter needle inserted in the second intercostal space (ICS) in the midclavicular line (MCL). However, due to variations of chest wall thickness, the 50mm needle-mounted catheter is insufficient and may only reach the pleural space. Objectives: To investigate whether the recommended anatomical site and the length of the angiocatheter used for patients in Western Cape, South Africa was optimal and explore alternative locations. Methods: We performed retrospective study measuring chest wall thickness (CWT) of adult patients treated for chest injuries in the Groote Schuur Hospital (GSH) trauma unit between 2014 and 2016. These patients underwent contrasted CT chest studies and image data were obtained via GSH Picture Archiving and Communication System. Multiple levels and sites of CWT were measured, using multiplanar CT acquisition. Patients with underlying chest wall pathology that is not trauma related, congenital anatomical abnormality, foreign bodies or partially imaged chest were excluded. Result: A total of 153 patients were eligible for the study. The mean ± SD chest wall thicknesses of the left and right 2nd ICS MCL were 41,03 ± 15,24mm and 41,77 ± 15,83mm, respectively. Thus, suggesting that 20.9% of patients (n=32) would fail needle decompression at 2nd ICS MCL. The average CWT of the 3rd ICS MCL, 4th ICS MCL, 4th ICS AAL, 4th ICS MAL, 5th ICS MCL, 5th ICS AAL, 5th ICS MAL were 33.95, 27.18, 34.41, 41.31, 21.68, 28.42 and 36.31mm, respectively. The location with the highest needle decompression failure rate was the right 4th ICS MAL (26.1%), whereas the lowest failure rate was the right 5th ICS MCL (3.9%). The location with the highest rate of organ injury was the 4th ICS MCL (26%), and the safest location was at the 4th ICS MAL with no organ injury. Conclusion: Failure rate for needle decompression using the traditional 14G 50 mm angiocatheter at the 2nd ICS MCL in the South African population is high. We recommend that needle decompression should be performed at the 5th ICS AAL, due to the low failure rate and reduced risk of iatrogenic organ injury.